(untitled) (Research, Society and Development, 2022)
The land use and occupation in watersheds directly influences the water resources, and the vegetation cover is a crucial factor for water maintenance. The objective of this study was to characterize the land use and occupation in nine watersheds of the Lower Iguaçu River (Andrada, Monteiro, Gonçalves Dias, Floriano, Silva Jardim, Cotejipe, Sarandi, Capanema and Santo Antônio sub-basin rivers), using the classification from satellite images. The classification area obtained high accuracy (Kappa coefficient of 99.4 to 99.9%). The Floriano River sub-basin presented the highest degree of environmental preservation, followed by Silva Jardim and Gonçalves Dias River sub-basins, fully or partially inserted in Iguaçu National Park. Monteiro and Sarandi river sub-basins showed the smallest areas of vegetation, and Capanema, Cotejipe, Andrada and Santo Antônio River sub-basins exhibited an intermediate condition. This tendency was verified by the cluster analysis. These results can serve as a baseline for planning, monitoring and management of this area, environmental modeling, conservation of water resources, biodiversity, and environmental services.